Recommendations of Polish experts for 2024 on the co-administration of vaccines in adults for the prevention of respiratory infections - Antczak, Adam; Konstanty, Mikołaj; Kuchar, Ernest; Mastalerz-Migas, Agnieszka; Nitsch-Osuch, Aneta; Parczewski, Miłosz; Wysocki, Jacek (Family Medicine & Primary Care Review, 2025)
In 2024, Polish experts updated their recommendations on co-administration of vaccines in adults to focus on preventing respiratory infections. These guidelines align with international standards from organizations such as the WHO, ECDC, and ACIP, reaffirming that administering multiple vac-cines in a single visit is safe and effective. Co-administration increases the likelihood of timely immunization, reducing missed opportunities to protect high-risk groups, particularly against dis-eases such as influenza, COVID-19, and pneumococcal infections. The COVID-19 pandemic high-lighted the vulnerability of adults to respiratory infections, especially the elderly and those with chronic conditions. Despite existing guidelines, vaccination coverage in Poland remains suboptimal. The co-administration approach aims to streamline the immunization process, improving vaccination rates while ensuring safety and efficacy. The guidelines outline the general principles of co-administration, noting that most vaccines can be given together safely, with some exceptions. For instance, pneumococcal conjugate and polysaccharide vaccines require staggered ad-ministration. They also address specific protocols for injection sites, contraindications, and special populations like pregnant women and individuals with asplenia. The recommendations urge healthcare providers to seize every opportunity to vaccinate adult patients, educate them on the risks of respiratory infections, and promote the benefits of co-administration. These guidelines seek to increase immunization rates and strengthen protection against respiratory diseases in adults by simplifying vaccination schedules.